Impact of Active Case Finding on Clinical Structure and Severity of Tuberculosis in School-Aged Children (7-15 Years Old) - V. А. Аksenova; А. V. Gordina; S. А. Sterlikov; D. А. Kudlay; D. А. Kucheryavaya; N. P. Doktorova (Туберкулез и болезни лёгких)
The objective: to evaluate the impact of active case finding in children 7-15 years old on the clinical structure of tuberculosis and epidemic risk of detected patients.Subjects and Methods: 1,679 children aged 7-15 ill with tuberculosis.Result. The following has been observed in active case finding of tuberculosis versus tuberculosis detection when the patient is seeking medical care: A 9-fold reduction in the risk of disseminated and generalized tuberculosis; a 4.5-fold reduction in the risk of epidemically dangerous cases of tuberculosis; a 6-fold reduction in the risk of destructive forms of pulmonary tuberculosis. Cases of extrapulmonary tuberculosis were more frequently detected when patients were seeking medical care.Thus, the strategy adopted in Russia for active tuberculosis detection in children leads to significant results: preventing the spread of tuberculous infection in children's communities and reducing the proportion of severe forms of tuberculosis that create the risk of disability and death from tuberculosis.